Development of a Powtoon-Based Learning Video Integrated with Nature of Science (NOS) on Cell Material - Fadya Puspita Ayu Fatimah; Dios Sarkity; Adam Fernando (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2026)
Integrating NOS into digital media is important for understanding abstract biological concepts and promoting scientific literacy. This study aimed to develop a Powtoon-based learning video integrated with the Nature of Science (NOS) on cell material for eighth-grade junior high school students and to determine the validity of the developed product. Previous research has developed Powtoon-based learning videos, but the integration of NOS into cell-related learning media remains limited. Therefore, this study offers a novel approach by developing NOS-integrated Powtoon videos to aid understanding of abstract cell concepts. This study employed a Research and Development (R&D) approach adapted from the ADDIE model, focusing on the analysis, design, and development stages. In the analysis stage, data were collected through teacher interviews, preliminary questionnaires, a literature review, and curriculum and content analyses using checklist sheets. Students' needs and characteristics were also identified through questionnaires. During development, the product was evaluated through expert validation by material and media experts using Likert-scale instruments. The data were analyzed quantitatively to determine validity levels and qualitatively based on feedback and suggestions from validators. Quantitative data were analyzed using percentage feasibility analysis based on expert validation scores, while qualitative data were analyzed descriptively through validator input and suggestions. Results showed that the developed learning video achieved material validity of 92.96% and media validity of 95.80%, both of which were categorized as very valid. The novelty of this study lies in integrating the NOS approach into a Powtoon-based animated video to support students' understanding of abstract biological concepts. Developed media can help teachers present cell material more visually and support students’ understanding of microscopic concepts and scientific processes. In conclusion, the developed media is considered valid and feasible at the development stage. Further research is recommended to examine its effectiveness in classroom implementation.